DIGITAL LITERACY IN ISLAMIC EDUCATION: ASSESSING THE EFFICACY OF ONLINE LEARNING PLATFORMS IN FOSTERING RELIGIOUSAND ACADEMIC DEVELOPMENT - Ali Muhdi; Musyarrafah Sulaiman Kurdi; Mardiah Mardiah; Ilham Kamaruddin; Yulian Purnama (International Journal of Teaching and Learning, 2023)
Digital literacy initiatives in Islamic education have emerged as dynamic endeavors to bridge the gap between tradition and modernity. This study assesses the efficacy of online learning platforms in fostering religious and academic development within Islamic education. Through a comprehensive exploration of diverse programs, case studies, challenges, and opportunities, the research seeks to provide valuable insights for educators, policymakers, and stakeholders invested in optimizing the integration of digital literacy. The study examines the impact on religious development, emphasizing the role of online platforms in Islamic studies, Quranic studies, Hadith integration, and the moral consciousness of students. Additionally, the research delves into the academic realm, evaluating the effectiveness of digital literacy initiatives in teaching STEM subjects, enhancing language skills, and enriching literature studies. The socio-cultural implications, including the influence on cultural preservation, stakeholder perceptions, and the need for cultural sensitivity, form an integral part of the study. The findings contribute to a nuanced understanding of the multifaceted impact of digital literacy on academic development within the unique framework of Islamic education.